Kajian Farmakoinformatika Senyawa Caulerchlorin dan Racemosin sebagai kandidat Antimalaria - Dewi Ratih Tirto Sari; Nadia Humairoh; Intani Quarta Lailaty; Gabriella Chandrakirana Krisnamurti; Siti Zamilatul Azkiyah (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
Caulerchlorin and racemosin were bioactive compounds containing in Caulerpa racemosa macroalgae. Previous study, those compounds promoted therapeutical target on metabolic syndrome. However, the therapeutical activity on Malaria not yet defined. Therefore, this study investigated potential activity of caulerchlorin and racemosin from Caulerpa racemosa as antimalarial activity through pharmacoinformatic study. Caulerchlorin and racemosin structures were retrieved from PubChem NCBI and the Plasmodium falciparum dihydroorotate dehydrogenase (PfDHODH) structure was taken out from Protein database with ID 5GJG. Orotic acid was used as native ligand or control. Ligands were predicted their antiplasmodial activity and toxicity. Ligands and protein were interacted by redocking using Molegro Virtual Docker version 6.0 and analyzed by using PyMol 2.3 and Discovery Studio version 21.1.1. Two bioactive compounds also showed antiplasmodial activity and were not mutagenicity and hepatotoxicity affections. Molecular docking performed that caulerchlorin and racemosin exhibited same active residues as well as orotic acid as native substrate. Binding energy revealed two compounds, caulerchlorin and racemosin showed lower binding energy than orotic acid. In summary caulerchlorin and racemosin were potentially inhibited PfDHODH activity by binding substrate sites of PfDHODH protein.